2022
DOI: 10.3389/fendo.2022.1016613
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and health outcomes: An umbrella analysis

Abstract: BackgroundThere is a relative lack of data that systematically investigates the breadth and validity of the association between bariatric surgery and health-related outcomes. We aimed to evaluate the quantity, validity, and credibility of evidence regarding the association between bariatric surgery and health-related outcomes using an umbrella review of meta-analyses.MethodsWe systematically searched PubMed, Embase, and the Web of Science databases from inception until December 2, 2021, to identify meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of the poor methodological quality of SRs in the food field are in line with those from assessments of the methodological quality of SRs that used the AMSTAR 2 tool in other fields, including acupuncture [16,17], dentistry [18], Tai Chi [19,20], surgery [21,22], major depression in adults [23], chronic obstructive pulmonary disease [24], cardiovascular risk [25], physical activity [26], pancreatic cancer [27], chronic heart failure [28], cancerrelated fatigue [29], Alzheimer's disease [30], chronic spinal pain [31], neonatal pain [32], hip fractures [33], and atopic eczema [34]. Although the target patients or participants and interventions in those studies differed between each study, all demonstrated that the majority of SRs included had low methodological quality ("low" or "critically low").…”
Section: Findings In Contextsupporting
confidence: 85%
“…However, there may be considerable correlations between the certainty of the results of the evidence and the results of quality assessments based on AMSTAR 2. Recently, many umbrella reviews have been performed that used both AMSTAR 2 and GRADE in healthcare settings [22,25,27,[32][33][34]. These studies were consistently determined to be "low" and "very low" according to the GRADE evaluation when the ratings were also "low" or "critically low" in AMSTAR 2.…”
Section: Relevance To the Grade Approach (Grading Of Recommendations ...mentioning
confidence: 99%
“…It is known that bariatric surgery is not only a restrictive surgery but also a metabolic surgery. 15 , 16 The authors suggest that the low plasma OPN levels observed in Group 1 composed of overweight individuals in the early postoperative period may be another favorable metabolic effect of bariatric surgery, independent of weight loss. This finding highlights the accuracy of the terminology “metabolically healthy obese”.…”
Section: Discussionmentioning
confidence: 99%
“…A previous umbrella review by Liao et al explored the impact of bariatric surgery on health outcomes 45 . However, they did not analyze the impact of different bariatric surgery procedures despite the variable mechanisms underlying each bariatric procedure.…”
Section: Discussionmentioning
confidence: 99%